SPESIALISASI MATERI AJAR SEBAGAI UPAYA PENGEMBANGAN PROFESIONALISME GURU - Das Salirawati (LPMPP Universitas Negeri Yogyakarta, 2008)
AbstractThe school-based curriculum gives teachers freedom to design and develop alllearning activities for students by themselves, so it is expected that the teacherscompetence can be improved optimally. Besides, teachers creativity andinnovation can be developed to increase their professionalism. But, the fact showsthat the teachers responsibility is so heavy that they do not have enough time todevelop their professionalism. Almost all SMPs/MTss and SMAs/MAs inIndonesia assign teachers some duties based on classes. One of the ways toimprove teachers mastery can be done by taking specialization in teachingmaterials. This method gives some advantages to teachers and students as well. Forthe teachers, specialization in teaching materials can make them: (1) concentrate onthe teaching material development; (2) plan learning strategies effectively; (3) lookfor references easily and attentively; (4) write summaries and modules; (5) selectseminars and workshops to attend; and (6) direct students based on their ability.For the students, specialization in teaching materials can make them: (1) get theunity of concepts from the same teacher; (2) avoid needless character adaptationfrom different teachers; (3) detect self-ability; (4) look for references easily; and (5)avoid from learning over-lapping concepts. It seems difficult to implementspecialization for teaching material, but by having a good intention to increaselearning quality in Indonesia, all difficulties and obstacles can be handled. Patienceand seriousness are really needed to start a new thing. Whatever the result is, thiseffort should be made.Keywords : specialization, effort, professionalism, teacher